2019
DOI: 10.20546/ijcmas.2019.808.045
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Bacterization of Rhizobium and Methylobacterium radiotolerans on Germination and Survivability in Groundnut Seed

Abstract: country (Sathya Priya, et al., 2013) and occupies first place in acerage (more than 28%). It is grown over an area of 5.31 million ha and producing 6.93 million tonnes of Peanut (DOAC, 2012) with productivity of 1305 kg/ha in Indian context. Its cultivation is mostly confined to the states of Gujarat,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 10 publications
1
6
0
2
Order By: Relevance
“…significantly increased the seedling height of red pepper and tomato . Priya et al, (2019) reported that the effect of single strain of M. radiotolerans in groundnut significantly increase the root and shoot length when compared to un-inoculated control. Inoculation of methylotrophic bacteria significantly enhanced the plant parameters of root and shoot length on groundnut (Krishnamoorthy et al, 2019).…”
Section: Root Shoot and Seedling Lengthmentioning
confidence: 98%
“…significantly increased the seedling height of red pepper and tomato . Priya et al, (2019) reported that the effect of single strain of M. radiotolerans in groundnut significantly increase the root and shoot length when compared to un-inoculated control. Inoculation of methylotrophic bacteria significantly enhanced the plant parameters of root and shoot length on groundnut (Krishnamoorthy et al, 2019).…”
Section: Root Shoot and Seedling Lengthmentioning
confidence: 98%
“…M. nodulans Crotalaria providing nitrogen; decreasing levels of ethylene [12,16,17] M. oryzae Rice increasing plant cytokinin levels; solubilizing phosphate [13,[18][19][20] M. extorquens Pine; Arabidopsis; Brassia inducing the expression of host defense genes [21,22] M. mesophilicum Sugarcane increasing plant cytokinin levels [23] M. radiotolerans Brassia; Combretaceae providing nitrogen; exhibited high antibacterial and antifungal activity; decreasing levels of ethylene [24,25] M. populi Brassia providing nitrogen [26] M. komagatae Brassia providing nitrogen [17] M. aquaticum Brassia providing nitrogen [17] M. funariae Moss increasing plant cytokinin levels [27] M. phyllosphaerae Rice decreasing levels of ethylene [28]…”
Section: Species Name Host Plants Effects On Host Plantsmentioning
confidence: 99%
“…Las semillas previamente seleccionadas fueron embebidas en el inoculo por una hora antes de realizar la siembra (Priya et al, 2019). Para la obtención de los diferentes inóculos, se partió de pre inóculos que se prepararon a partir de una asada de las cepas, conservadas en tubos con medio Levadura Manitol (LM) (Vincent, 1970) sólido a 4 ºC, en frascos Erlenmeyers de Research, Society and Development, v. 10, n. 6, e10110615722, 2021 (CC BY 4.0) | ISSN 2525-3409 | DOI: http://dx.doi.org/10.33448/rsd-v10i6.15722 4 100 mL de capacidad que contenían 10 mL del mismo medio de cultivo líquido.…”
Section: Tratamiento a La Semillaunclassified
“…Los rizobios son una de estas bacterias que tienen la capacidad de colonizar activamente el sistema radicular para favorecer su crecimiento y rendimiento de plantas no leguminosas (Pérez et al, 2019). Bacterias del género Rizobios han sido empleadas para estimular el desarrollo de diversas especies de plantas como Moringa oleifera Lam (Mazher et al, 2014), Theobroma cacao (Suprano et al, 2015), Oryza sativa L. (Hernández y Nápoles, 2017), Arachis hypogaea L. (Priya et al, 2019), Zea mays L. (Pérez et al, 2019), Vigna unguiculata L. Walp. (Hara et al, 2021), entre otros.…”
Section: Introductionunclassified